2007
DOI: 10.1029/2006ja012141
|View full text |Cite
|
Sign up to set email alerts
|

Dayside reconnection enhancement resulting from a solar wind dynamic pressure increase

Abstract: It is well known that the Interplanetary Magnetic Field (IMF) is the major contributor to geomagnetic activity on Earth. Recent studies, however, have shown that solar wind dynamic pressure variations also cause global effects when they encounter the terrestrial magnetosphere. In particular, it has been shown that solar wind dynamic pressure enhancements significantly increase particle precipitation and cause global intensification of the aurora. Further studies using Defense Meteorological Satellite Program (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 39 publications
6
66
0
Order By: Relevance
“…These oscillations periodically separate and bring together the closed and open field lines on the two sides of the coronal hole boundary. This picture is somewhat similar to what is seen in the magnetosphere: a sudden increase in the solar wind pressure during southward interplanetary magnetic field orientation leads to enhanced magnetic reconnection on the dayside magnetopause (Boudouridis et al 2005). Hence, the proposed mechanism explains the repetitive nature of the observed EEs, however, other possibilities should not be excluded.…”
Section: Discussionsupporting
confidence: 59%
“…These oscillations periodically separate and bring together the closed and open field lines on the two sides of the coronal hole boundary. This picture is somewhat similar to what is seen in the magnetosphere: a sudden increase in the solar wind pressure during southward interplanetary magnetic field orientation leads to enhanced magnetic reconnection on the dayside magnetopause (Boudouridis et al 2005). Hence, the proposed mechanism explains the repetitive nature of the observed EEs, however, other possibilities should not be excluded.…”
Section: Discussionsupporting
confidence: 59%
“…In particular, Bosqued et al (2005) reported about CLUSTER observations of transient reconnection signatures in the Cusp region, which are often one to one correlated with repeated pressure variations, during a strongly B y dominated period. Further to that, Boudouridis et al (2007) clearly showed that, for B z <0, the pressure variations are often directly related to variations of the dayside reconnection rate. Finally, we recall that Laitinen et al (2007) suggest that higher values of solar wind dynamic pressure yield increased reconnection rates at the magnetopause for B z <0 and that the dominant parameter to account for such increased rates is solar wind velocity rather than density.…”
Section: Araki-type and Tcv-like Effectsmentioning
confidence: 99%
“…[e.g., Boudouridis et al, 2007]. For a linear system the factor a would be independent of the state of the magnetosphere (and hence the substorm phase); however we note that the theories of voltage saturation predict that a falls with increasing F O [Siscoe et al, 2004] and hence increasing F PC .…”
Section: Expanding-contracting Polar Cap Modelmentioning
confidence: 99%